IMPLEMENTASI PENGELOLAAN PENGETAHUAN DI PTPN 7 LAMPUNG DALAM MENGHADAPI GLOBALISASI BISNIS - Admin APERTI (JURNAL TEKNOLOGIA, 2018)
Knowledge management in an organisation/firm has an important role to create and maintain competitive advantages in the global market. The main objectives of knowledge management are to maintain firm’s dynamic and competitiveness, to facilitate knowledge culture and improvement of human resource performances, to get added values and to create new and integrated inovation. Using primary data from the field trip, this paper aims to (1) identify implementation of knowledge management in PTPN 7 Lampung; and (2) provide implication for decision makers in PTPN 7 Lampung to maximize knowledge management of the human resources. Implementation of knowledge in PTPN 7 Lampung has been conducted. However some obstacles have been occured particularly in relating/combining individual and group knowledges that can be managed to be firm’s advantages. The obstacle can cause organisation fails to gain sustainable innovation. Internal improvement is needed in order to implement the fourth knowledge management elements i.e, socialization, externalization, combination and internalization.